Open Data in musikphilologischen Projekten: Herausforderungen, Strategien, Potenziale - Kepper, Johannes; Münzmay, Andreas (DHd2023: Open Humanities, Open Culture)

Kirche und Musiktheater. Ein ambivalentes Verhältnis in Schlaglichtern - Adler, Luise; Tumat, Antje (Loccumer Pelikan. Religionspädagogisches Magazin für Schule und Gemeinde des Religionspädagogischen Instituts Loccum)

The Identification of a New Liquid Metal Embrittlement (LME) Type in Resistance Spot Welding of Advanced High-Strength Steels on Reduced Flange Widths - Yang, Keke; Meschut, Gerson; Seitz, Georg; Biegler, Max; Rethmeier, Michael (Metals (Special Issue Embrittlement Phenomena in Steel Metallurgy))

ProDaZ Online-Tool Technik - Heil, Rebekka; Prange, Sarah-Christin

ProDaZ Online-Tool Pflege. - Heil, Rebekka

Dynamic conformity assessment for joining force monitoring using Bayes filters - Butzhammer, Lorenz; Kappe, Fabian; Meschut, Gerson; Hausotte, Tino (Materials Research Proceedings)
Monitoring force-displacement or force-time curves is a widely used quality control technique in the field of mechanical joining. For online monitoring of self-piercing riveting, envelope curves are often used to define a tolerance zone for the measured setting force. However, the measurement uncertainty is typically not considered and the force curve of a joint can be wrongly rated as non-conform due to measurement errors and noise. In this article, we present a method for dynamical online filtering and uncertainty determination for noisy force curves using two types of Bayesian filters. The methodology is based on a Bayesian probability framework using a priori information for the process curve and sensor noise. To investigate the general feasibility of the method, force measurements with different noise levels are simulated and processed. The conformity is further assessed taking the uncertainty of the filtered signal into account. The results show that the Bayes filter technique is principally able to reduce noise for well-known characteristics of the process curve and sensor noise. Advantages over common filtering techniques, especially for experimental conditions with less known characteristics, are still to be verified. The methodology could be used in future for closed-loop controls to adapt process parameters dynamically.

Combination of versatile self-piercing riveting processes - Wituschek, Simon; Kappe, Fabian; Meschut, Gerson; Lechner, Michael (Materials Research Proceedings)
Due to economic and ecological framework conditions, a resource-saving utilization of raw materials and energy is becoming increasingly important in particular in the mobility sector. For the reduction of moving masses and the resources consumed, lightweight construction technologies are part of modern production processes in vehicle manufacturing, for example in the form of multi-material systems. Challenging in the manufacture of multi-material systems especially in view of changing supply chains is the variety of materials and geometries that bring conventional joining processes to their limits. Therefore, new processes are required, which can react versatile to process and disturbance variables. A widely used industrial joining process is semi-tubular self-piercing riveting, which is however a rigid process. To increase the versatility, the two newly established processes multi-range self-piercing riveting and tumbling self-piercing riveting are combined and the capabilities for targeted material flow control are united. Therefore, an innovative two-stage process based on the combination is introduced in this paper. The rivet is set with the multi-range self-piercing riveting process with an overlap of the rivet head and then formed by a tumbling process. Further, a specific adaptation of the tumbling strategy is used to investigate the possibility of reducing cracks in the rivet head. Thereby, different tumbling strategies are used and similar geometric joint formations are achieved to compare the results.

On the Multimodal Resolution of a Search Sequence in Virtual Reality - Klowait, Nils (Human Behavior and Emerging Technologies)
In virtual reality (VR), participants may not always have hands, bodies, eyes, or even voices—using VR helmets and two controllers, participants control an avatar through virtual worlds that do not necessarily obey familiar laws of physics; moreover, the avatar’s bodily characteristics may not neatly match our bodies in the physical world. Despite these limitations and specificities, humans get things done through collaboration and the creative use of the environment. While multiuser interactive VR is attracting greater numbers of participants, there are currently few attempts to analyze the in situ interaction systematically. This paper proposes a video-analytic detail-oriented methodological framework for studying virtual reality interaction. Using multimodal conversation analysis, the paper investigates a nonverbal, embodied, two-person interaction: two players in a survival game strive to gesturally resolve a misunderstanding regarding an in-game mechanic—however, both of their microphones are turned off for the duration of play. The players’ inability to resort to complex language to resolve this issue results in a dense sequence of back-and-forth activity involving gestures, object manipulation, gaze, and body work. Most crucially, timing and modified repetitions of previously produced actions turn out to be the key to overcome both technical and communicative challenges. The paper analyzes these action sequences, demonstrates how they generate intended outcomes, and proposes a vocabulary to speak about these types of interaction more generally. The findings demonstrate the viability of multimodal analysis of VR interaction, shed light on unique challenges of analyzing interaction in virtual reality, and generate broader methodological insights about the study of nonverbal action.
Keywords: Human-Computer Interaction; General Social Sciences; Social Psychology; Virtual Reality : Multimodality; Nonverbal Interaction; Search Sequence; Gesture; Co-Operative Action; Goodwin; Ethnomethodology

First steps towards real-time assessment of attentional weights and capacity according to TVA - Banh, Ngoc Chi; Scharlau, Ingrid (Abstracts of the 65th TeaP)

Emerging disciplinary voices - Stock, Ingrid; Karsten, Andrea; Eik-Nes, Nancy Lea (Sakprosa)
While referencing is an important feature of academic writing, many students struggle with using sources. This struggle seems to be due, in part, to the tension students experience when advised to cite sources (i.e., others’ voices) on the one hand, and to demonstrate their own disciplinary voice on the other hand. The aim of this article is to contribute to the understanding of source use, presenting a figure that illustrates gradients of students’ engagement with sources in various sections of their bachelor’s theses. Based on Bakhtin’s idea that a writer’s voice gradually emerges out of others’ words, and the terms knowledge telling and knowledge transforming, we developed a continuum that might help to understand the complexity of source use. We arrived at this continuum through the qualitative exploration of students’ use of sources in 15 bachelor’s theses from the humanities in one Norwegian university. In this article, we illustrate the continuum through extracts from the students’ theses, showing how issues of voice are intertwined with students’ engagement with sources. We propose that understanding the various functions of sources as they are typically used in the disciplines will help students to develop and demonstrate their disciplinary voices. Moreover, the continuum provides a foundation for fruitful discussions of writing practices that raise critical awareness about implicit expectations concerning source use and issues of voice in academic writing.
Keywords: Automotive Engineering

Voices in Dialogue: Taking Polyphony in Academic Writing Seriously - Karsten, Andrea (Written Communication)
In the past decades, the notion of voice in the theorizing and teaching of academic writing has been the subject of much debate and conceptual change, especially concerning its relation to writer identity. Many newer accounts of voice and identity in academic writing draw on the dialogical concept of voice by Bakhtin. However, some theoretical and methodological inconsistencies have surfaced in the adaptions of the concept. Working from a refinement of the dialogical notion of voice based on the concepts of polyphony and interiorization, this article presents a methodological approach for analyzing voice(s) in writing. The article presents material around the evolution of an early-career researcher’s dissertation synopsis. The material is multilayered, including the writer’s text, transcripts from an interdisciplinary peer-feedback conversation with two colleagues, and a video-stimulated interview with the writer. Excerpts of the material were analyzed to trace the polyphony of interiorized voices that influenced the writing. This focus revealed the multivoicedness of academic texts as an effect of their history of coming into being. This article contributes to the question of voice and identity in academic writing from a dialogical psycholinguistic perspective by presenting a de-reifying notion of voice grounded in an understanding of writing as a polyphonic activity, which also feeds into the formation of a writer’s self.
Keywords: Literature and Literary Theory; Communication

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.
Keywords: Additive Manufacturing; Laser Sintering; Filled Materials; Composites; Polyamide 613

Halogen-Free Flame Retardant Powder Materials for Laser Sintering: Evaluation and Process Stability Analysis - Neitzel, Fabian; Kletetzka, Ivo; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
The high flammability of components manufactured by laser sintering (LS) using standard polyamide 12 (PA12) powder still severely restricts their use in industries such as electronics, aviation, and transportation. A key factor for the further establishment of LS is the expansion of the material portfolio with, for example, refreshable and halogen-free flame-retardant (FR) powder materials. Accordingly, various halogen-free FRs are investigated in this work and evaluated with respect to their use in LS. First, their decomposition behavior and mode of action are examined. Subsequently, the additives are dry blended with PA12 to investigate properties relevant for LS, such as particle morphology, thermal behavior and melt viscosity. Afterwards, test specimens for UL94 vertical flame-retardancy tests are produced by processing the dry blends on an EOS P3 LS system. Finally, the process stability of the process-aged powder blends is investigated by again examining the thermal behavior and melt viscosity.
Keywords: Additive Manufacturing; Laser Sintering; Flame Retardant; Polyamide 12

Coworking - Krause, Ina (Arbeit)
Zusammenfassung Der Beitrag beschäftigt sich mit dem Konzept Coworking und arbeitet auf Basis eigener empirischer Daten heraus, wie dieses Konzept im Zuge seiner wachsenden Verbreitung und der Etablierung von Coworking-Spaces als ‚dritten Orten der Arbeit‘ Legitimität für neue Gestaltungsideen und Wertvorstellungen von Büroarbeit generiert. Coworking-Spaces werden dabei als ‚dritte Orte‘ definiert, die dem Raumkonzept der Schaffung einer flexibel anpassbaren und Kreativität fördernden Arbeitsumgebung für Büroarbeiter:innen folgen. Das Geschäftskonzept Coworking-Space wird inzwischen aber auch als alternatives Organisationsmodell von Arbeit wahrgenommen. Dem Beitrag liegt das Forschungsinteresse zugrunde zu erkunden, wie und in welchen Variationen das Konzept Coworking in Büroarbeitsorganisationen, die sich selbst als Coworking-Space bezeichnen, adaptiert und praktisch umgesetzt wird. Nachgezeichnet wird, inwiefern Coworking als alternatives Gestaltungsmodell oder, im Sinne von Meyer und Rowan, Rationalisierungskonzept der Organisation von Arbeit Elemente eines neuen Normalitätsverständnisses von Büroarbeit generiert, welches über Betreiber:innen von Coworking-Spaces und Coworker:innen inzwischen in die Breite der Arbeitsgesellschaft getragen wird.
Keywords: Industrial and Manufacturing Engineering

Im Osten nichts Neues? Über (un)bekannte Akteure in der regionalen Weiterbildungslandschaft. - Krause, Ina; Biess, Anne; Bohlinger, Sandra (bwp@ Berufs- und Wirtschaftspädagogik – online)

Entkoppelte Arbeitswelten - Krause, Ina
Die Strukturen der industriell geprägten Arbeitsgesellschaft werden durch den zunehmenden Einsatz automatisierter und digitaler Technologien sowie den Ausbau der Infrastruktur des Internets maßgeblich verändert. Gleichzeitig lässt sich eine intensive Flexibilisierung vertrauter Strukturen betriebszentrierter Organisationsformen von Beschäftigung beobachten. Ina Krause beschreibt einzelne Dynamiken auf der gesellschaftlichen Mesoebene und trägt damit zur Debatte über die nachhaltige Gestaltung der digitalen und virtuellen Arbeitsgesellschaft in Deutschland bei.

Frontmatter - Krause, Ina; Jacobsen, Heike; Gerhards, Christian (Arbeit)
Keywords: Industrial and Manufacturing Engineering

Turnover-Based Corporate Income Taxation and Corporate Risk-Taking - Amberger, Harald; Siahaan, Fernando; Sureth-Sloane, Caren

Business Reputation Systems based on Blockchain Technology—A Risky Advance - Hemmrich, Simon (Proceedings of 31st European Conference on Information Systems (ECIS 2023))
Reputation is indispensable for online business since it supports customers in their buying decisions and allows sellers to justify premium prices. While IS research has investigated reputation systems mainly as review systems on online platforms for business-to-consumer (B2C) transactions, no proper solutions have been developed for business-to-business (B2B) transactions yet. We use blockchain technology to propose a new class of reputation systems that apply ratings as voluntary bonus payments: Before a transaction is performed, customers commit to pay a bonus that is granted if a service provider has performed a service properly. As opposed to rival reputation systems that build on cumulated ratings or reviews, our system enables monetized reputation mechanisms that are inextricably linked with online transactions. We expect this system class to provide more trustworthy ratings, which might reduce agency costs and serve quality providers to establish a reputation towards new customers, building on second-order trust.
Keywords: Trust; Risk; Reputation System; Blockchain Technology; Business Reputation System.

Nonlinear Dielectric Geometric-Phase Metasurface with Simultaneous Structure and Lattice Symmetry Design - Liu, Bingyi; Geromel, René; Su, Zhaoxian; Guo, Kai; Wang, Yongtian; Guo, Zhongyi; Huang, Lingling; Zentgraf, Thomas (ACS Photonics)
In this work, we utilize thin dielectric meta-atoms placed on a silver substrate to efficiently enhance and manipulate the third-harmonic generation. We theoretically and experimentally reveal that when the structural symmetry of the meta-atom is incompatible with the lattice symmetry of an array, some generalized nonlinear geometric phases appear, which offers new possibilities for harmonic generation control beyond the accessible symmetries governed by the selection rule. The underlying mechanism is attributed to the modified rotation of the effective principal axis of a dense meta-atom array, where the strong coupling among the units gives rise to a generalized linear geometric phase modulation of the pump light. Therefore, nonlinear geometric phases carried by third-harmonic emissions are the natural result of the wave-mixing process among the modes excited at the fundamental frequency. This mechanism further points out a new strategy to predict the nonlinear geometric phases delivered by the nanostructures according to their linear responses. Our design is simple and efficient and offers alternatives for the nonlinear meta-devices that are capable of flexible photon generation and manipulation.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

The role of digital technologies in transforming student learning landscapes - Rezat, Sebastian; Geiger, Vince (Handbook of Digital Resources in Mathematics Education)

Implementing profession orientation as a design principle for overcoming Klein’s second discontinuity – preservice teacher’s perspectives on interface activities in the context of a geometry course - Hoffmann, Max; Biehler, Rolf (ZDM – Mathematics Education)
Intending to counteract Klein’s second discontinuity in teacher education, we explored and applied the innovation of “interface ePortfolio” in the context of a geometry course for preservice teachers (PSTs). The tool offers the possibility of implementing the design principle of profession orientation. In the article, we theoretically clarify what we understand by this principle and locate our innovative concept against this theoretical background. We empirically investigate the extent to which counteraction against the second discontinuity is successful by analyzing reflection texts created in the interface ePortfolio, focusing on PSTs’ perspectives. Our qualitative content analysis shows that most of them perceive the innovation as helpful in the intended sense and indicates that the course concept, in general, and the interface ePortfolio, in particular, have helped establish relevant links between the course content and their later work as teachers.
Keywords: General Mathematics; Education

Towards comparable ratings: Exploring bias in German physician reviews - Kersting, Joschka; Maoro, Falk; Geierhos, Michaela (Data & Knowledge Engineering)
In this study, we evaluate the impact of gender-biased data from German-language physician reviews on the fairness of fine-tuned language models. For two different downstream tasks, we use data reported to be gender biased and aggregate it with annotations. First, we propose a new approach to aspect-based sentiment analysis that allows identifying, extracting, and classifying implicit and explicit aspect phrases and their polarity within a single model. The second task we present is grade prediction, where we predict the overall grade of a review on the basis of the review text. For both tasks, we train numerous transformer models and evaluate their performance. The aggregation of sensitive attributes, such as a physician’s gender and migration background, with individual text reviews allows us to measure the performance of the models with respect to these sensitive groups. These group-wise performance measures act as extrinsic bias measures for our downstream tasks. In addition, we translate several gender-specific templates of the intrinsic bias metrics into the German language and evaluate our fine-tuned models. Based on this set of tasks, fine-tuned models, and intrinsic and extrinsic bias measures, we perform correlation analyses between intrinsic and extrinsic bias measures. In terms of sensitive groups and effect sizes, our bias measure results show different directions. Furthermore, correlations between measures of intrinsic and extrinsic bias can be observed in different directions. This leads us to conclude that gender-biased data does not inherently lead to biased models. Other variables, such as template dependency for intrinsic measures and label distribution in the data, must be taken into account as they strongly influence the metric results. Therefore, we suggest that metrics and templates should be chosen according to the given task and the biases to be assessed.
Keywords: Language model fairness; Aspect phrase classification; Grade prediction; Physician reviews

Verifying Software and Reconfigurable Hardware Services - Wehrheim, Heike; Platzner, Marco; Bodden, Eric; Schubert, Philipp; Pauck, Felix; Jakobs, Marie-Christine (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

On-The-Fly Computing -- Individualized IT-services in dynamic markets - Haake, Claus-Jochen; Meyer auf der Heide, Friedhelm; Platzner, Marco; Wachsmuth, Henning; Wehrheim, Heike
In the proposal for our CRC in 2011, we formulated a vision of markets for IT services that describes an approach to the provision of such services that was novel at that time and, to a large extent, remains so today: „Our vision of on-the-fly computing is that of IT services individually and automatically configured and brought to execution from flexibly combinable services traded on markets. At the same time, we aim at organizing markets whose participants maintain a lively market of services through appropriate entrepreneurial actions.“ Over the last 12 years, we have developed methods and techniques to address problems critical to the convenient, efficient, and secure use of on-the-fly computing. Among other things, we have made the description of services more convenient by allowing natural language input, increased the quality of configured services through (natural language) interaction and more efficient configuration processes and analysis procedures, made the quality of (the products of) providers in the marketplace transparent through reputation systems, and increased the resource efficiency of execution through reconfigurable heterogeneous computing nodes and an integrated treatment of service description and configuration. We have also developed network infrastructures that have a high degree of adaptivity, scalability, efficiency, and reliability, and provide cryptographic guarantees of anonymity and security for market participants and their products and services. To demonstrate the pervasiveness of the OTF computing approach, we have implemented a proof-of-concept for OTF computing that can run typical scenarios of an OTF market. We illustrated the approach using a cutting-edge application scenario – automated machine learning (AutoML). Finally, we have been pushing our work for the perpetuation of On-The-Fly Computing beyond the SFB and sharing the expertise gained in the SFB in events with industry partners as well as transfer projects. This work required a broad spectrum of expertise. Computer scientists and economists with research interests such as computer networks and distributed algorithms, security and cryptography, software engineering and verification, configuration and machine learning, computer engineering and HPC, microeconomics and game theory, business informatics and management have successfully collaborated here.

Compute Centers I: Heterogeneous Execution Environments - Hansmeier, Tim; Kenter, Tobias; Meyer, Marius; Riebler, Heinrich; Platzner, Marco; Plessl, Christian (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Flexible Industrial Analytics on Reconfigurable Systems-On-Chip - Boschmann, Alexander; Clausing, Lennart; Jentzsch, Felix; Ghasemzadeh Mohammadi, Hassan; Platzner, Marco (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

Mikroformen des Praxisbezugs im Lehramtsstudium in NRW. Eine Bestandsaufnahme anhand der bildungswissenschaftlichen Studienanteile des Studiengangs HRSGe - Homt, Martina (die hochschullehre)
Im Zusammenhang mit dem Lehramtsstudium wird häufig ein mangelnder Praxisbezug kritisiert und dabei vornehmlich auf schulische Praxisphasen als sogenannte Makroformen des Praxisbezugs rekurriert. Eine Auseinandersetzung mit Mikroformen auf der curricularen Ebene findet hingegen kaum statt. Um einen Überblick über Mikroformen des Praxisbezugs zu erhalten, wird unter Rück griff auf Zielperspektiven der Lehrkräftebildung ein Analyserahmen mit den Kategorien Praxis als Bezugspunkt von Themen, Praxis als Gegenstand der Auseinandersetzung mit Themen, Praxis als Gegenstand von Erprobung sowie Praxis als Gegenstand von Analyse und Reflexion entwickelt und auf das intendierte Curriculum der lehramtsausbildenden Hochschulen in NRW in Form von Prüfungsordnungen als rahmensetzende Grundlage für die Planung von Studienangeboten angewandt. Die inhaltsanalytische Auswertung zeigt, dass alle Kategorien in den Prüfungsordnungen thematisiert werden, jedoch in unterschiedlicher Intensität. Die Befunde werden mit Blick auf die Zielperspektiven des Lehramtsstudiums, die begriffliche Unschärfe von Praxisbezug sowie Konsequenzen für die Ausgestaltung des Studienangebots auf Ebene des implementierten Curriculums diskutiert.

Tiere in der Theologie? Zur Überwindung der Tiervergessenheit. Der Blog des Zentrums für Komparative Theologie und Kulturwissenschaften - Herdramm, Henrike (BloKK. Der Blog des Zentrums für Komparative Theologie und Kulturwissenschaften)

Ästhetik digitaler Medien. Aktuelle Perspektiven - Flath, Beate

Gegen das Verstummen. Texthermeneutische Reflexionen zu Ironie in der Textsortenwelt des Gettos Litzmannstadt - Markewitz, Friedrich
Unmittelbar nach der nationalsozialistischen Machtergreifung setzte eine umfassende gesellschaftliche, juristische und existentielle Ausgrenzung jüdischer Akteure ein. Dem Zerbrechen bisheriger Welt- und Normverständnisse zu begegnen wurde zu einer existentiellen Herausforderung sowie zu einem notwendigen Bedürfnis. Eine wichtige Strategie war der Einsatz von Humor und Ironie; auch für die Menschen des Gettos Litzmannstadt. Aus texthermeneutischer, kulturlinguistischer und sprachphilosophischer Perspektive erfasst Friedrich Markewitz – unter Berücksichtigung des Gettos als Diskursraum und dessen Textsortenwelt – Verwendungsweisen und -funktionen von Ironie und perspektiviert sie, um so einen Beitrag zur linguistischen Aufarbeitung der Kommunikation jüdischer Akteure während der Shoa zu leisten.

Kommunikative Praktiken im Nationalsozialismus
Die nationalsozialistische Gesellschaft war geprägt von vielgestaltigen kommunikativen Praktiken des sozialen und auch gewaltvollen Ein- und Ausschlusses. Gleichzeitig bildeten sich durch Widerstandshandlungen vielfältige Gegendiskurse heraus. Der Sammelband nimmt konkrete Beispiele kommunikativer Praktiken während des Nationalsozialismus in den Blick und fragt speziell danach, inwiefern diese themen-, textsorten- und akteursspezifisch gebunden waren

„Die Juden 'leben' bei ihrer betont rechnerischen Begabung am längsten schon nach dem Rasseprinzip, weshalb sie sich auch am heftigsten gegen die uneingeschränkte Anwendung zur Wehr setzen“ - Pragmalinguistische Perspektiven auf kommunikative Ausgrenzungs- und Invektivitätspraktiken in der veröffentlichen wie unveröffentlichten textgebundenen Kommunikation Martin Heideggers - Markewitz, Friedrich (Kommunikative Praktiken im Nationalsozialismus)
Invektivitäts-, Aggressions- und Gewaltpraktiken sind als sozial-kommunikative zugleich universelle Phänomene. Als kommunikative Praktiken bestimmt, können sie direkte An- griffe, z. B. in Form rassistischer und sexistischer Kommentare, aber auch indirektere Formen und Muster der Ab- wie Ausgrenzung umfassen. Ziel des Beitrags ist die Erfassung, Einordnung und Kategorisierung kommunikativer Invektivitätshandlungen in den tex- tuellen Kommunikaten Martin Heideggers. Die Linguistik kann in diesem Kontext pro- duktiv dazu beitragen, die Umfassenheit, Ausdifferenziertheit und strukturelle Relevanz der Invektivitäts- wie Gewaltsprachhandlungen als kommunikative Praktiken dieses Phi- losophen aufzuarbeiten und würde dahingehend auf bestehende Forschungsdesiderata reagieren, da sich trotz der Affinität Heideggers zu Fragen des Sprachlichen bisher kaum sprachwissenschaftliche Analysen finden, die Heidegger(s Schriften) zum Analysegegen- stand hatten. Dabei sollen nicht nur explizite Formen kommunikativen Invektivitätshan- delns erfasst werden, sondern ebenso indirektere Formen der Exklusion und Antihuma- nität, die als Teil des differenzphilosophischen Programms Heideggers als Ausgrenzungs- erfahrungen reflektiert werden können.

Zur Verwendung von wörtlicher und imaginierter (Gegen-)Rede in Tarnschriften des kommunistischen und sozialistischen Widerstands - Markewitz, Friedrich; Wilk, Nicole M. (Kommunikative Praktiken im Nationalsozialismus)
Der Beitrag bestimmt anhand der für den kommunistischen und sozialistischen Wider- stand gegen die Hitler-Diktatur charakteristischen Textgattung Tarnschrift die für den Widerstandskontext noch nicht untersuchten kommunikativen Praktiken des Gegenre- dens. Gegenreden wird in seiner dialogischen und responsiven Qualität sowohl aus text- typologischer Perspektive beschrieben als auch am Beispiel der Re-Inszenierung durch direktes und indirektes Referat interaktionslinguistisch gefasst. Schließlich werden auf- grund dieser kritischen, opponierenden und teilweise ironisierenden Bezugnahmen von Tarnschriftenartikeln auf Inhalte des NS-Diskurses und der Propaganda Tarnschriften als kommunikative Gattung der Gegenrede bestimmt. Die kommunikative Praktik des Ge- genredens wird dahingehend präzisiert, dass sie strukturell eine »Ursprungsrede« insze- niert und ein Verfahren der Gegenrede beinhaltet, mit dem sich eine widerstandsspezifi- sche Diskursposition oft auch durch das Aufdecken von Widersprüchen vollzieht. In einer Korpusanalyse von 125 Tarnschriften wird die Varianz der dialogischen Gestaltungsver- fahren des Gegenredens anhand von redeanzeigenden Verben und redebezeichnenden Nomen als Kookkurrenten von Namen wichtiger NS-Funktionäre erfasst.

“Er ist doch ohne Übertreibung die Personifikation des Kategorischen Imperativs. Possibilities and limits of inner-discourse critique on the basis of selected textual communicates of the Litzmannstadt ghetto - Markewitz, Friedrich (Proceedings of the Conference Language and Power)
While forms of resistance and criticism of Nazi actors by jewish prisoners in concentration camps and jewish ghetto inhabitants have already been described, linguistic analyses of communicative conflicts within ghettos are still mostly lacking. Conflicts existed not only because of the heterogeneous social, ethnic, etc. compositions of the ghettos, but also because of internal power struggles. A power hierarchy arising from these struggles within the ghetto can be demonstrated for the Polish ghetto Litzmannstadt: a “ghetto elite” stood in sharp contrast to the majority of the ghetto population. In the context of this proceedings paper, the possibilities and limits of inner-discursive forms of critique on the basis of the power-axis “ghetto-elite”-ghetto-population will be reflected. During this, a contrastive perspective will be additionally adopted in order to compare different text genres, such as the diary, but also the ghetto chronicle and the ghetto encyclopedia, which are unique to the Litzmannstadt ghetto. These texts differ, among other things, in their degree of publicity and thus offer the possibility of being able to grasp the various conditions, functions, possibilities and limits of inner- discursive criticism of power.

Einleitung - Markewitz, Friedrich; Scholl, Stefan; Schubert, Katrin; Wilk, Nicole M. (Kommunikative Praktiken im Nationalsozialismus)

Der Text - Markewitz, Friedrich (Journal für Medienlinguistik)

Pantheon - Süßmann, Johannes

Mutation Tree Reconstruction of Tumor Cells on FPGAs Using a Bit-Level Matrix Representation - Opdenhövel, Jan-Oliver; Plessl, Christian; Kenter, Tobias (Proceedings of the 13th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies (HEART))

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 10,2: Zettelsammlung aus den Synopsen der Manuskriptbände I bis X, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2023, xv, 229–475 S - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete, Zbl. 1527.01035)

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 10,1: Zettelsammlung aus den Synopsen der Manuskriptbände I bis X, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2023, xviii, 225 S - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete, Zbl 1527.01036)

Modeling Appropriate Language in Argumentation - Ziegenbein, Timon; Syed, Shahbaz; Lange, Felix; Potthast, Martin; Wachsmuth, Henning (Proceedings of the 61st Annual Meeting of the Association for Computational Linguistics)
Online discussion moderators must make ad-hoc decisions about whether the contributions of discussion participants are appropriate or should be removed to maintain civility. Existing research on offensive language and the resulting tools cover only one aspect among many involved in such decisions. The question of what is considered appropriate in a controversial discussion has not yet been systematically addressed. In this paper, we operationalize appropriate language in argumentation for the first time. In particular, we model appropriateness through the absence of flaws, grounded in research on argument quality assessment, especially in aspects from rhetoric. From these, we derive a new taxonomy of 14 dimensions that determine inappropriate language in online discussions. Building on three argument quality corpora, we then create a corpus of 2191 arguments annotated for the 14 dimensions. Empirical analyses support that the taxonomy covers the concept of appropriateness comprehensively, showing several plausible correlations with argument quality dimensions. Moreover, results of baseline approaches to assessing appropriateness suggest that all dimensions can be modeled computationally on the corpus.

Neural Class Expression Synthesis in ALCHIQ(D) - Kouagou, N'Dah Jean; Heindorf, Stefan; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (Machine Learning and Knowledge Discovery in Databases: Research Track)
Class expression learning in description logics has long been regarded as an iterative search problem in an infinite conceptual space. Each iteration of the search process invokes a reasoner and a heuristic function. The reasoner finds the instances of the current expression, and the heuristic function computes the information gain and decides on the next step to be taken. As the size of the background knowledge base grows, search-based approaches for class expression learning become prohibitively slow. Current neural class expression synthesis (NCES) approaches investigate the use of neural networks for class expression learning in the attributive language with complement (ALC). While they show significant improvements over search-based approaches in runtime and quality of the computed solutions, they rely on the availability of pretrained embeddings for the input knowledge base. Moreover, they are not applicable to ontologies in more expressive description logics. In this paper, we propose a novel NCES approach which extends the state of the art to the description logic ALCHIQ(D). Our extension, dubbed NCES2, comes with an improved training data generator and does not require pretrained embeddings for the input knowledge base as both the embedding model and the class expression synthesizer are trained jointly. Empirical results on benchmark datasets suggest that our approach inherits the scalability capability of current NCES instances with the additional advantage that it supports more complex learning problems. NCES2 achieves the highest performance overall when compared to search-based approaches and to its predecessor NCES. We provide our source code, datasets, and pretrained models at https://github.com/dice-group/NCES2.

Extremwettersituationen in alpinen Gebieten: Management kritischer Situationen in Echtzeit bei extremen und komplexen Daten - Pottebaum, Jens; Rechberger, Christina; Hieb, Michael; Gräßler, Iris; Resch, Christian (Tagungsband der Fachtagung Katastrophenforschung 2023)
Extremwettersituationen sind durch die Kombination von globalen und lokalen Wirkzusammenhän-gen gekennzeichnet. In der Gefahrenanalyse und -reaktion ist deshalb der Umgang mit extremen Daten erforderlich, die von heterogenen Datenquellen bezogen und mittels unterschiedlicher Ver-fahren bis hin zum maschinellen Lernen ausgewertet werden. Die Visualisierung dieser zwangsläufig unsicherheitsbehafteten Daten stellt eine Herausforderung dar. Diese wirkt umso bedeutsamer, je weniger Fachexpertise in Bereichen wie Meteorologie, Geologie oder Sensortechnik in einer Füh-rungs- oder Leitstelle eingebunden werden kann. Das Management kritischer Situationen in Echtzeit bei extremen und komplexen Daten muss daher auf einer Bewertung der Informationsqualität von extremen Daten beruhen. Diese Bewertung ist abhängig vom Anwendungskontext in unterschiedli-chen Führungs- und Assistenzstellen sowie der verfügbaren Infrastruktur mit Geräten zur Visualisie-rung, Schnittstellen von Wetterdiensten, Sensorsysteme und Rettungsrobotik. Im Beitrag wird der Ansatz des EU-Projekts CREXDATA in Bezug auf mögliche pluviale Hochwassersituationen in Inns-bruck vorgestellt. Grundlage bildet die Kategorisierung von extremen Daten, die Schnittstellen zu Datenquellen mit globalem und lokalem Bezug sowie Anwendungsfälle für die Visualisierung von Informationen. Es werden somit Grundlagen präsentiert, die in allen Formen von geobasierten Lage- und Führungsinformationssystemen zum Einsatz kommen können.

Multi-stage diarization refinement for the CHiME-7 DASR scenario - Boeddeker, Christoph; Cord-Landwehr, Tobias; von Neumann, Thilo; Haeb-Umbach, Reinhold (7th International Workshop on Speech Processing in Everyday Environments (CHiME 2023))

Explaining ELH Concept Descriptions through Counterfactual Reasoning - Sieger, Leonie Nora; Heindorf, Stefan; Blübaum, Lukas; Ngonga Ngomo, Axel-Cyrille (arXiv:2301.05109)
Knowledge bases are widely used for information management on the web, enabling high-impact applications such as web search, question answering, and natural language processing. They also serve as the backbone for automatic decision systems, e.g. for medical diagnostics and credit scoring. As stakeholders affected by these decisions would like to understand their situation and verify fair decisions, a number of explanation approaches have been proposed using concepts in description logics. However, the learned concepts can become long and difficult to fathom for non-experts, even when verbalized. Moreover, long concepts do not immediately provide a clear path of action to change one's situation. Counterfactuals answering the question "How must feature values be changed to obtain a different classification?" have been proposed as short, human-friendly explanations for tabular data. In this paper, we transfer the notion of counterfactuals to description logics and propose the first algorithm for generating counterfactual explanations in the description logic $\mathcal{ELH}$. Counterfactual candidates are generated from concepts and the candidates with fewest feature changes are selected as counterfactuals. In case of multiple counterfactuals, we rank them according to the likeliness of their feature combinations. For evaluation, we conduct a user survey to investigate which of the generated counterfactual candidates are preferred for explanation by participants. In a second study, we explore possible use cases for counterfactual explanations.

Accelerating Concept Learning via Sampling - Baci, Alkid; Heindorf, Stefan (CIKM)

Viele Bedürfnisse, eine Gesundheit - Mombeck, Mona Maria (Greencare)

Digital Transformation - Towards flexible human-centric enterprises - Kehrbusch, Burkhard; Engels, Gregor (Digital Transformation: Core Technologies and Emerging Topics from a Computer Science Perspective)

Optimization of optical waveguide antennas for directive emission of light - Farheen, Henna; Leuteritz, Till; Linden, Stefan; Myroshnychenko, Viktor; Förstner, Jens (Journal of the Optical Society of America B)
Optical traveling wave antennas offer unique opportunities to control and selectively guide light into a specific direction, which renders them excellent candidates for optical communication and sensing. These applications require state-of-the-art engineering to reach optimized functionalities such as high directivity and radiation efficiency, low sidelobe levels, broadband and tunable capabilities, and compact design. In this work, we report on the numerical optimization of the directivity of optical traveling wave antennas made from low-loss dielectric materials using full-wave numerical simulations in conjunction with the particle swarm optimization algorithm. The antennas are composed of a reflector and a director deposited on a glass substrate, and an emitter placed in the feed gap between them serves as an internal source of excitation. In particular, we analyze antennas with rectangular- and horn-shaped directors made of either hafnium dioxide or silicon. The optimized antennas produce highly directional emissions due to the presence of two dominant guided TE modes in the director in addition to leaky modes. These guided modes dominate the far-field emission pattern and govern the direction of the main lobe emission, which predominately originates from the end facet of the director. Our work also provides a comprehensive analysis of the modes, radiation patterns, parametric influences, and bandwidths of the antennas, which highlights their robust nature.
Keywords: tet_topic_opticalantenna